2020
DOI: 10.1002/jsfa.10714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moro orange juice (Citrus sinensis(l.) Osbeck) on some metabolic and morphological parameters in obese and diabetic rats

Abstract: BACKGROUNDNutritional intervention with the use of phytochemicals is an important method for the treatment and prevention of a metabolic syndrome. The objective of this study was to chemically characterize Moro orange juice. The influence of juice intake on metabolic parameters of rats that were obese, diabetic or both by means of body mass management after the activation of anthocyanins during refrigerated storage was also assessed.RESULTSJuice intake reversed most of the metabolic abnormalities exhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In experimental models, the nutritional intervention with Moro orange juice was able to reverse most of the metabolic abnormalities related to obese rats, including reduced body mass and improved biochemical profile (decreased triacylglycerol (21.35%), total cholesterol (14.0%) and LDL-cholesterol (16.2%) and increase in HDL-cholesterol) ( Magalhães et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental models, the nutritional intervention with Moro orange juice was able to reverse most of the metabolic abnormalities related to obese rats, including reduced body mass and improved biochemical profile (decreased triacylglycerol (21.35%), total cholesterol (14.0%) and LDL-cholesterol (16.2%) and increase in HDL-cholesterol) ( Magalhães et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Reduction of hepatic cholesterol content, cholesterol esterification and increase the activity of LDL receptors (decreases the plasma concentrations of remaining chylomicrons and LDL). [( Magalhães et al, 2020 )] Citrus sinensis Human 250 mL–700 mL or 400 mg Approximately 12 weeks Orange juice or dry extract of Moro orange juice Few evidences and non-significant results associated with anthropometric measurements. Improvement of the biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several reported beneficial effects of ROC have attracted scientific attention, such as its anti-inflammatory properties, anti-oxidant activity, and cardiovascular protection [ 12 16 29 30 31 32 33 ]. In this study, we evaluated the effects of 13-week oral ROC administration on UV-irradiated skin damage in Skh:HR-2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moro orange is a rich source of active compounds such as hydroxycinnamic acid, flavone glycosides and ascorbic acids, including anthocyanins with an average content of about 140 mg/L [ 18 , 19 , 20 , 21 ]. Evidence to date has shown that blood oranges demonstrate potent antioxidant activity and cytoprotective effects that reflect their substantial role in preventing chronic pathological conditions such as cardiovascular diseases and in many forms of cancers [ 21 , 22 , 23 , 24 , 25 ]. Moreover, a recent study showed that a red orange standardized extract is able to inhibit 3T3-L1 differentiation, by downregulating adipogenic gene and enzymes together with the modulation of adiponectin secretion and leptin release [ 26 ].…”
Section: Introductionmentioning
confidence: 99%